A Systematic Review of Research to Determine Toxicity of Involuntary Tobacco Smoking as Compared to First Hand Smoking and if Chronic Involuntary Tobacco Smoking during Childhood Causes Skeletal Diseases Later in Life - Bobzien, Michael J. (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
A healthy adult life depends on a healthy childhood. Toxic exposures during childhood impact human development and negatively impact adulthood. It is important to be aware of the impact of toxic exposures children may be exposed to. A child will breath up to 3 times the volume per body weight compared to an adult and take in the same ratio of airborne toxicants. A child’s organs and immune system are not fully developed to offer protection from airborne and residual toxins compared to an adult. Children have limited options to escape toxins if they are in the home. Thus, children are the most susceptible to the effects of toxins in their environment and should be protected from such exposures. Comprehensive literature review utilizing google scholar searching the terms; secondhand smoke, tobacco smoke, passive smoking, cadmium, lead, mercury, polycyclic aromatic hydrocarbons, osteoporosis, osteoarthritis, and arthritis. Results: Tobacco Smoke exposure is the greatest toxic exposure risk a child faces in a home environment. Tobacco Smoke exposure starts in the womb when the embryo embeds in the mother’s uterus and connects to their mother’s blood flow. Tobacco smoke contains many osteotoxic, nephrotoxic, cytotoxic, and genotoxic chemicals that significantly alter genetic material in the developing fetus and child having long term consequences. Involuntary smoking is more of a health risk than active smoking. Children in the home environment are more vulnerable to the toxins produced by active smokers even if the smoking takes place when the child is not physically in the home. The child’s toxic exposure has long-term health effects leading to poor bone health and skeletal diseases later in life. As parents and members of the general public we need to implement safeguards to protect children in the home from involuntary tobacco smoking.